Pharmacodynamics and clinical effectiveness of clopidogrel and atorvastin in patients with acute coronary syndrome and hyperlipidaemia - A. S. Sivkov; S. V. Paukov; R. Sh. Balugyan; V. G. Kukes; M. V. Zhuravleva; S. I. Sivkov; T. N. Farafonova (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To study pharmacodynamics and clinical effectiveness of clopidogrel and atorvastatin in patients with acute coronary syndrome (ACS) and hyperlipidaemia (HLP).Material and methods. The study included 90 patients with ACS and Type IIA or IIB HLP. Group I received clopidogrel monotherapy, Group II — a combination of clopidogrel and atorvastatin, and Group III — atorvastatin monotherapy. Blood lipid profile (LP), induced platelet aggregation (IPLA), and cytochrome P-450 3A4 isoenzyme were measured.Results. Clopidogrel did not affect blood LP, but significantly reduced IPLA. Its effectiveness was also demonstrated in combination with atorvastatin, despite reduced activity of cytochrome P-450 3A4 isoenzyme. Lipidlowering effect of atorvastatin was observed both for monotherapy and its combination with clopidogrel. Atorvastatin monotherapy has a mild anti-aggregant effect: IPLA was reduced as early as during the third month of the treatment.Conclusion. High effectiveness of an anti-platelet agent clopidogrel and a lipid-lowering medication atorvastatin opens a window for their wide use in cardiologic practice, in particular, for ACS patients.